Quantitative Relationship Between Domestic Energy Consumption and the Standard of Living in Hungary - Domán, Csaba (Theory, Methodology, Practice – Review of Business and Management, 2012)
The changes in the energy consumption prices in the last few decades have caused a lot of trouble for the citizens. We can observe an undesirable tendency in energy prices indicated by the collective effect of several factors. This leads to difficulties for residents, because their income has not followed the rise of the energy prices. The problem is even worse regarding the fact that a significant part of residential use depends on fossil fuels. Only a small percentage of the citizenship can afford to supply their energy needs from new types of fuels. This paper attempts to determine a relationship between the population’s standard of living and energy consumption in Hungary.